Knowledge, attitudes, and willingness of community pharmacy staff in Mures County, Romania, to provide the brief advice to stop smoking: A cross-sectional study - Nădășan Ingrid; Ferencz Loránd; Moldovan Geanina; Ábrám Zoltán; Nădășan Valentin (Acta Marisiensis - Seria Medica, 2023)
Background and objective: Providing brief advice to stop smoking (BASS) can significantly increase motivation to quit, long-term smoking cessation rates, and substantially impact public health. The study aimed to evaluate knowledge, attitudes, and willingness of community pharmacy staff in Mures County, Romania, to provide BASS to smokers.